If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(y + 5) = 8y + -6 Reorder the terms: 9(5 + y) = 8y + -6 (5 * 9 + y * 9) = 8y + -6 (45 + 9y) = 8y + -6 Reorder the terms: 45 + 9y = -6 + 8y Solving 45 + 9y = -6 + 8y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8y' to each side of the equation. 45 + 9y + -8y = -6 + 8y + -8y Combine like terms: 9y + -8y = 1y 45 + 1y = -6 + 8y + -8y Combine like terms: 8y + -8y = 0 45 + 1y = -6 + 0 45 + 1y = -6 Add '-45' to each side of the equation. 45 + -45 + 1y = -6 + -45 Combine like terms: 45 + -45 = 0 0 + 1y = -6 + -45 1y = -6 + -45 Combine like terms: -6 + -45 = -51 1y = -51 Divide each side by '1'. y = -51 Simplifying y = -51
| 125*.38= | | -2x+2(-4x-3)=74 | | 4(y-8)=9+5y | | 28-6(2x+4)= | | 3(x+2)=4(x+2) | | 2x-1=63 | | z-(2+1i)z+(-1+7i)=0 | | 3(d-0.8)=4x+4 | | -34+3x=18+5x | | 19.3-4.507= | | 5x-31=2x+8 | | x+73=3x+9 | | 1-a^2=x^2-2ax+1 | | -6(2t+6)=-12 | | 3r=-18 | | x=7y-47 | | 0.14y+0.07(y+6000)=1260 | | 12-3(4x+2)=3x+4(x-8) | | 3[x+5(6-x)+24]-11=79-15x | | 3-y=6y+7 | | 4(-18+24)= | | 2x-70=50+6x | | (-6+12i)(-7-9i)=0 | | 2x^3-3x=6x^2 | | 6r^2+12r+24=0 | | -(9-6a)-(10+5a)-14=-(2-6a)+(-a)+1 | | -5(n+4)+22=-3n-4 | | 15x-2(x+1)=154 | | 14x-4(4x-2)=5(2x+1)+3 | | 20.00-1.45*v=1.15 | | -9x-156=42-2x | | 14x-3(x+1)=96 |